Race and schooling in the South, 1880-1950 : an economic history - Margo, Robert A. (Robert Andrew), 1954- (NBER series on long-term factors in economic development., 1990)
The interrelation among race, schooling, and labor market opportunities of American blacks can help us make sense of the relatively poor economic status of blacks in contemporary society. The role of these factors in slavery and the economic consequences for blacks has received much attention, but the post-slave experience of blacks in the American economy has been less studied. To deepen our understanding of that experience, Robert A. Margo mines a wealth of newly available census data and school district records. By analyzing evidence concerning occupational discrimination, educational expen.